Answer:
a) y = |x/2 -2| +4
b) y = |x/2 -2| +2
c) y = |(x+1)/2 -2| +3
d) y = |(x-1)/2 -2| +3
Step-by-step explanation:
To translate the function f(x) by (h, k) in the (right, up) direction, you transform it to ...
g(x) = f(x -h) +k
a) one unit up
Add 1 to the function value.
[tex]y=\left|\dfrac{x}{2}-2\right|+3+1\\\\\boxed{y=\left|\dfrac{x}{2}-2\right|+4}[/tex]
b) one unit down
Subtract 1 from the function value.
[tex]y=\left|\dfrac{x}{2}-2\right|+3-1\\\\\boxed{y=\left|\dfrac{x}{2}-2\right|+2}[/tex]
c) one unit left
Replace x with x-(-1).
[tex]y=\left|\dfrac{x-(-1)}{2}-2\right|+3\\\\\boxed{y=\left|\dfrac{x+1}{2}-2\right|+3}[/tex]
d) one unit right
Replace x with x-1.
[tex]\boxed{y=\left|\dfrac{x-1}{2}-2\right|+3}[/tex]